18F-Florbetapir Binds Specifically to Myocardial Light Chain and Transthyretin Amyloid Deposits. (August 2015) - Park, Mi-Ae; Padera, Robert F.; Belanger, Anthony; Dubey, Shipra; Hwang, David H.; Veeranna, Vikas; Falk, Rodney H.; Di Carli, Marcelo F.; Dorbala, Sharmila
<x xml:space="preserve">Abstract</x> Background— 18F-florbetapir is a promising imaging biomarker for cardiac light chain amyloidosis (AL) and transthyretin amyloidosis (ATTR). Our aim, using human autopsy myocardial specimens, was to test the hypothesis that 18F-florbetapir binds specifically to myocardial AL and ATTR amyloid deposits. Methods and Results— We studied myocardial sections from 30 subjects with autopsy-documented AL (n=10), ATTR (n=10), and nonamyloid controls (n=10) using 18F-florbetapir and cold florbetapir compound and digital autoradiography. Total and nonspecific binding of 18F-florbetapir was determined using the maximum signal intensity values. Specific binding of 18F-florbetapir was calculated by subtracting nonspecific from total binding measurements (in decays per minute/mm2, DPM mm2) and was compared with cardiac structure and function on echocardiography and the histological extent of amyloid deposits. Diffuse or focally increased 18F-florbetapir uptake was noted in all AL and ATTR samples and in none of the control samples. Compared with control samples, mean 18F-florbetapir–specific uptake was significantly higher in the amyloid samples (0.94±0.43 versus 2.00±0.58 DPM/mm2; P<0.001), and in the AL compared with the ATTR samples (2.48±0.40 versus 1.52±0.22 DPM/mm2; P<0.001). The samples from subjects with atypical echocardiographic features of amyloidosis showed quantitatively more intense 18F-florbetapir–specific uptake compared with control samples (1.50±0.17 versus 0.94±0.43 DPM/mm2; P=0.004), despite smaller amyloid extent than in subjects with typical echocardiograms. Conclusions— 18F-florbetapir specifically binds to myocardial AL and ATTR deposits in humans and offers the potential to screen for the 2 most common types of myocardial amyloid.